4
$\begingroup$

Factorise $9x-x^3$ completely.

It's simple but I'm never seem to get it right; I've got $(x-1)(-x+9)x$.

$\endgroup$
11
$\begingroup$

$$9x-x^3 = x(9-x^2)=x(3-x)(3+x)$$

where in the last step I have used the very important and useful "difference of two squares" identity:

$$ (A-B)(A+B)=A^2-B^2 $$

$\endgroup$
2
$\begingroup$

Notice that $9 - x^2$ is the product of $(3 - x)(3+x)$

$$9 x - x^3 =x (9 - x^2) = x(3-x)(3+x)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.